Treasury Management Practices at Universiti Utara Malaysia - Wan Mustaffa, Wan Yusoff (2006)
The purpose of the study is to evaluate the effectiveness of treasury management practices at Universiti Utara Malaysia (UUM). Respondents of the research are the Bursar and a senior officer of the UUM’S Bursar Department. The type of research is a comparative study and the instruments of information collection used were through questionnaires and interviews. Descriptive method was employed in analyzing the data. The gathered information was compared with the Code of Practice on Treasury management by The Chartered Institute of Public Finance and Accountancy (CIPFA), which is being adopted by University of Oxford, United Kingdom. Result of the research shows that the UUM’S Bursar Department does not fully adopted all the Code of Practice on Treasury management by The Chartered Institute of Public Finance and Accountancy (CIPFA). However, UUM has partially adopted the treasury management practices such as in cash flow forecasting, investment, money laundering, staff training, reporting, performance measurement, and budgeting, accounting and auditing. This study is able to create awareness in understanding the importance and the function of treasury management. In reality, treasury management practice becomes more relevant to UUM in view that its stakeholder, the Government of Malaysia, might reduce future financial assistance. Moreover, UUM is already experiencing reduction of financial resources from government. Therefore, to ensure the optimal practice of treasury management, a framework on treasury management has been established to act as a guidance for the Bursar Department of UUM. Lastly, further research need to be done involving other public higher education institutions, so that a standard policy on treasury management practices for the whole public higher education institutions in Malaysia can be made a reality.